RESPONSE OF SHAREHOLDER VALUE VARIATION FOR INFLATION IN THE IRAQI ECONOMY MEDIATED BY STOCKS PRICING EFFICIENCY - Mustafa Hussein Hassan; Estabraq Mahmood Jarallah; Haider Nassrullah Dawood (American Journals, 2024)
The aims of research test the effect of Inflation as one of the macroeconomic factors affecting investment activities, on shareholder value that measured by of Economic value added as a primary goal that the company seeks to maximize through achieving a return on capital that exceeds its cost in the stock market, and the extent of the change that occurs when entering Efficiency of stock pricing as a mediating variable, so in order to test the relationship of influence, the researcher intended to identify (10) institutions works in the Iraqi market and shares are registered in the Iraq Stock Exchange for the period extending from (2011-2020) monthly, from different sectors (banking, industrial, service), so The data will be of the type (Panel Data) with number of observations (1200), to measurement of inflation variable was using the consumer price index, shareholder value variable by added market value, and the pricing efficiency variable by the Treynor model, so for testing the mediation hypotheses using dynamic models were adopted, specifically the generalized moments model (GMM), results showed that there is a direct positive effect of inflation on shareholder value, as well as an indirect positive effect of inflation on shareholder value through pricing efficiency.
Keywords: Shareholder value, inflation, pricing efficiency, economic value added, generalized moments model.